The oil palm loose fruit collector machine / Zulhusni Samsor and Haszeme Abu Kasim - Samsor, Zulhusni; Abu Kasim, Haszeme (School of Mechanical Engineering, 2023)
The oil palm plantation is a crucial economic contributor and natural catchment area for Malaysia. However, due to the industry's outdated technology and traditional approach in collecting loose fruit, younger generations may not find it attractive. Thus, this project aims to improve the design of loose fruit collection devices. The current traditional method of collecting by hand is time-consuming and can cause back pain. Therefore, the project's objective is to design and fabricate tools that make loose fruit collection easier, increase the amount collected, easy to handle, and portable to reduce the risk of back pain and fatigue. The engineering calculation was conducted based on selected dimensions, and the loose fruit collector machine was fabricated for testing and analysis. The project has the potential to enhance and modernize technical systems into more functional tools.